A cohort study of BMI changes among U.S. Army soldiers during the COVID-19 Pandemic - Marc Wuerdeman; Amanda Banaag; Miranda Lynn Janvrin; Tracey Pérez Koehlmoos (BMC, 2023)
Abstract Background The increasing number of individuals with obesity is a healthcare concern in the United States (U.S.) population; the men and women who serve in the Army are no exception, with 17.3% of soldiers categorized with a body mass index (BMI) of Obesity in 2017. The COVID-19 pandemic profoundly disrupted life around the globe. During the pandemic, restrictions to soldier movement and activity were put in place to limit COVID-19 transmission. We strive to assess what effects these changes may have had on the BMIs of soldiers. Methods We conducted a retrospective cohort study of active duty U.S. Army soldiers using data from the Military Health System Data Repository. BMI was calculated and categorized before (February 2019 - January 2020) and during the pandemic (September 2020 - June 2021). Women who were pregnant or delivered during and one year prior to the study periods were excluded. Statistical analyses included paired t-tests evaluating mean BMI, percent change, and the Stuart-Maxwell test for marginal homogeneity. Results 191,894 soldiers were included in the cohort. During the pandemic, 50.5% of soldiers in the cohort were classified as Overweight and 23.2% were classified as Obesity. T-test and Stuart-Maxwell test indicated significant differences and changes in BMI categories between the pre-pandemic and pandemic periods, particularly the Obesity category, which experienced a 5% growth and 27% change. Significant absolute changes were observed during the pandemic; 26.7% of soldiers classified as Healthy weight in the pre-pandemic period shifted to Overweight in the pandemic period and 15.6% shifted from Overweight in the pre-pandemic period to Obesity in the pandemic period. Absolute increases were observed across every demographic category in soldiers with obesity; the categories that saw the highest increases were female, ages 20-24, White, and Junior Enlisted soldiers. Conclusions Higher rates of obesity may result in decreased health of the force. The specific needs of younger and Junior Enlisted soldiers need to be further addressed, with focus on special intervention programs by the U.S. Army.